Impact of marketing capabilities on competitive advantage: A case of Thai SME durian exporters - Kunanusorn, Anusorn; Puttawong, Duangporn; Li, Shaoyun (Edelweiss Applied Science and Technology, 2024)
Purposes of this study were to highlight the role of durian exporters’ marketing capabilities in achieving competitive advantage among Thai SMEs, and to describe the significance of a competitive advantage in achieving marketing goals by examining marketing capabilities. One hundred SME exporters were randomly selected from the list of firms listed on the Association of the Durian Exporters. Ninety-six questionnaires were included in this study. The PLS-SEM Program was used to analyze the collected data which was collected by using a mail questionnaire distributed to SME exporters. Results from data analysis were: 1) it indicated that all marketing capabilities, including product, price, distribution, and promotional capabilities, impacted competitive advantage; and 2) five competitive advantage forces were found to have statistically significant impacts. Moreover, the analysis confirmed that marketing capabilities and competitive advantages were related. Implications from this study were: 1) exporters find their endeavors to develop marketing strategies to achieve competitiveness in the global market; and 2) exporters could focus on distribution capabilities to survive and to expand their product to gain a competitive advantage in the marketplace. The limitation of this study was that this study did not involve quality assurance and variety of the durian, which would affect price capacity.